(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2020)
The Hirak, a peaceful protest movement that has been marching in Algerian streets for thirteen months, was compelled to give up its weekly demonstrations due to the spread of the Coronavirus pandemic. However, this obstacle did not represent a setback for the movement. Conversely, it led it to an evolution, transforming it into a Hirak “behind closed doors”. Although the movement has reacted adequately so far, what will remain of the Hirak once the emergency phase will end is still a question to be answered. There are three possible scenarios: its disappearance, its victory or the resumption of the status quo as it was before the pandemic.